A Follow-up Study of Neonatal Interatrial Shunt with Echocardiography until Twelve to Fifteen Months of Age - Chi-Lin Ho; Sheng-Ling Jan; Ming-Chih Lin; Yun-Ching Fu (Elsevier, 2008)
To assess the incidence and natural history of full-term neonates with interatrial shunt (IAS). Methods: A follow-up study of 1389 neonates who received screening echocardiography between 2003 and 2006. Babies with IAS at 2 to 4 days of life underwent follow-up echocardiography at 2 to 4 months, 6 to 9 months and 12 to 15 months of age until closure of IAS. Results: The ratio of IAS was 68.3% initially. No significant demographic differences were identified between infants with and without initial IAS. Among 949 neonates with initial IAS, 84.5% infants had a left-to-right interatrial shunt, 13.5% had bidirectional shunt and 2% had predominantly right-to-left shunt. The persistence rate of IAS at 12 to 15 months of age was 3.8% (44/1166). The initial size of IAS ranged from 1.2 to 7.7 mm (4.3 ± 1.1 mm) detected by color Doppler flow mapping and cases were divided into three groups: small (≦5 mm), medium (5 to 8 mm) and large group (≧8 mm). There were 74.6% infants in the small group and 25.4% in the medium group initially. The neonates in the initial small group would always see their IAS close or else they would remain in the small group. Those in the final medium and large size groups always came from the initial medium group. The late closure rate of IAS was 93.9% of infants with initial IAS. The closure curves of initial small and medium sized groups were significantly different, and their late closure rates were 95.1% and 90.4%, respectively. Conclusions: IAS was very common during early neonatal stage, but most cases would close after 1 year. The late closure rate of initial IAS was different if using a cutpoint of 5 mm.